The impact of meaningfulness and attractiveness of products' attributes on consumers' preferences - Wanat, Tomasz (Economics and Business Review, 2008)
Consumer judgment is often based on incomplete or limited knowledge of the relevant attributes. To recognize the impact of meaningless attributes a study was conducted. Results of the study show that ambiguous information can be taken into consideration in the decision making process. The willingness to use meaningless information is to a higher degree determined by perceived attractiveness rather than by the level of comprehension. Among the three types of meaningless attributes' information (numerical, descriptive and name) the one called "name" was characterized by the highest level of attractiveness and the lowest level of comprehension. The opposite effect was observed with numerical information which was considered as the least attractive but the most comprehensive. (original abstract)